Investigation of the effects of indoor air stability on the airborne transmission of droplets from violent respiratory events - Xiaorui Deng; Guangcai Gong; Xudong Yang (Indoor Environments)
Indoor air stability is a condition under which the indoor temperature gradients can affect the trajectories of constant breathing flows. However, it remains unclear how indoor air stability affects the airborne contaminants from violent respiratory events such as coughing. Here, we report a study of the dispersion of airborne droplets from coughing under different indoor air stability conditions. The distributions of droplets from coughing processes under stable and unstable conditions were compared. The results revealed that the stable conditions confined the coughed droplets to the breathing zone of the droplet host, whereas the unstable conditions intensified the dispersion of droplets and reduced their local concentration. The dimensionless vertical distance of the droplet cloud under the stable condition was 4 times longer than that of the unstable condition at t = 15 s. In addition, we observed that high ventilation rate caused an intense mixing of the indoor air, thus weakening the effect of indoor air stability on the propagation of droplet cloud. Personal exposure of the stable condition was 6.5 times larger than that of the unstable condition at a ventilation rate of 2.1 ACH, while it decreased to lower than half of that of the unstable condition at 7.1 ACH and 12.3 ACH. Personal exposure to the indoor environment should be assessed by simultaneously considering the indoor air stability conditions and ventilation rates. This study has provided insights into the transmission of cough droplets in indoor environments and has practical significance for preventing the spread of contagious diseases.